TEACHERS’ CONSTRAINTS IN THE IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS IN EFL CLASSROOMS - Hilma Suryani (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
The current study aimed to investigate the constraints that the EFL teachers encountered during the implementation of higher order thinking skills. This study employed purposive sampling. It involved twelve English teachers from five senior high schools. The participants were selected based on their teaching experience and the accreditation status of their schools. All participants were teaching in schools designated as Sekolah Penggerak, which are part of an Indonesian government initiative to drive educational improvement. Data were gathered through classroom observations and semi-structured interviews, then analysed using thematic analysis to identify recurring patterns and key issues. The analysis revealed three main constraints in the implementation of HOTS-based learning: (1) linguistic challenges, including students’ limited vocabulary, grammatical difficulties, and pronunciation issues that hindered active participation in critical thinking tasks; (2) heterogeneous language proficiency levels among students, making it difficult for teachers to deliver lessons that met the needs of all learners equally; and (3) time constraint, especially regarding the planning and execution of lessons that require deeper thinking and active student engagement. These findings highlight the need for more targeted language support for students, differentiated teaching strategies, and improved time management or curriculum adjustments to support the effective integration of HOTS in EFL classrooms.